Multimodal user interfaces to improve social integration of elderly and mobility impaired - Dias, J.; Pires, C.G.; Pinto, F.M.; Teixeira, V.D.; Freitas, J. (pHealth 2012: Proceedings of the 9th International Conference on Wearable Micro and Nano Technologies for Personalized Health, 2012)
Technologies for Human-Computer Interaction (HCI) and Communication have evolved tremendously over the past decades. However, citizens such as mobility impaired or elderly or others, still face many difficulties interacting with communication services, either due to HCI issues or intrinsic design problems with the services. In this paper we start by presenting the results of two user studies, the first one conducted with a group of mobility impaired users, comprising paraplegic and quadriplegic individuals; and the second one with elderly. The study participants carried out a set of tasks with a multimodal (speech, touch, gesture, keyboard and mouse) and multi-platform (mobile, desktop) system, offering an integrated access to communication and entertainment services, such as email, agenda, conferencing, instant messaging and social media, referred to as LHC - Living Home Center. The system was designed to take into account the requirements captured from these users, with the objective of evaluating if the adoption of multimodal interfaces for audio-visual communication and social media services, could improve the interaction with such services. Our study revealed that a multimodal prototype system, offering natural interaction modalities, especially supporting speech and touch, can in fact improve access to the presented services, contributing to the reduction of social isolation of mobility impaired, as well as elderly, and improving their digital inclusion.